Mechanical properties and thermal stability of tungsten boride films deposited by radio frequency magnetron sputtering. Issue 16 (November 2018) - Chrzanowska-Giżyńska, Justyna; Denis, Piotr; Woźniacka, Stefania; Kurpaska, Łukasz
Abstract: Tungsten and boron compounds belong to the group of superhard materials since their hardness could exceed 40 GPa. In this study, the properties of the tungsten boride WBx coatings deposited by radio frequency magnetron sputtering were investigated. The sputtering was performed from specially prepared targets that were composed of boron and tungsten mixed in a molar ratio of 2.5 and sintered in Spark Plasma Sintering (SPS) process. WB films were deposited on silicon (100) and stainless steel 304 substrates at temperatures of 23 ÷ 770 °C. Microstructure, chemical and phase composition were investigated by using Scanning Electron Microscope (SEM), X-Ray Photoelectron Spectroscopy (XPS) and X-Ray Diffraction (XRD), respectively. The mechanical properties like Vickers hardness and Young's modulus were obtained by using nanoindentation test at a load of 5 ÷ 100 mN. The friction coefficient and wear resistance of αWB coatings were investigated in scratch test and reciprocal sliding wear instrumentation. Moreover, in order to investigate thermal properties, the αWB films were annealed at 1000 °C in argon/air for 1 h and at 250 °C for 2 h in air atmosphere. Results of our research confirm that αWB coatings can be considered as an alternative to superhard materials in the production of wear resistant, long-lasting tools.